AB0649 Serum GDF-15 Level in Behçet's Disease: Relationship Between the Disease Activity and Clinical Parameters. (9th June 2015) - Sarıyıldız, M.A.; Yazmalar, L.; Batmaz, I.; Alpaycı, M.; Burkan, Y.K.; Sula, B.; Kaplan, I.; Yıldız, M.; Akar, Z.A.; Bozkurt, M.
Abstract : Background: Growth differentiation factor (GDF)-15, a member of the transforming growth factor-β superfamily of cytokines, plays an important role in cell growth, signal transduction, and apoptosis regulation. Objectives: The aim of this study was to evaluate serum GDF-15 levels and their relationship with disease-related variables in patients with Behçet's disease (BD). Methods: Forty-six patients diagnosed with BD and 30 demographically matched healthy control subjects participated in the study. GDF-15 levels were measured in blood samples from patients and controls. Behçet's Disease Current Activity Form (BDCAF) was used to evaluate the disease activity of BD. Results: There were no significant differences between the two groups in regard to C-reactive protein (CRP), mean erythrocyte sedimentation rate, age, body mass index and mean GDF-15 levels (p>0.05). The serum GDF-15 levels were positively correlated with peripheral arthritis, CRP, BDCAF erythema nodosum, BDCAF arthralgia, and BDCAF arthritis scores. The patients with BD were divided into twogroups according to the presence of peripheral arthritis; nine subjects (20%) were positive for peripheral arthritis. Serum ESR, CRP, white blood cell, and GDF-15 levels were significantly higher in the group that was positive for peripheral arthritis (p<0.05). Conclusions: GDF-15 may play a role in the progression and pathway of Behçet's joint involvement and erythema nodosum independent of classic inflammatory response measures. References: Wong RC, Ellis CN, Diaz LA et al Behcet's disease. Int J Dermatol 1984; 23: 25–32. Takeuchi M, Keino H, Suzuki J et al. Possibility of inducing anterior chamber-associated immune deviation by TGF-beta 2 treatment of monocytes isolated from Behcet's patients. Exp eye res 2006; 83: 981–988 Yazmalar L, Batmaz I, Sarıyıldız MA et al. Sleep quality in patients with Behçet's disease. Int J Rheum Dis 2014; doi: 10.1111/1756-185X.12459. Canete JD, Celis R, Noordenbos T et al. Distinct synovial immunopathology in Behçet disease and psoriatic arthritis. Arthritis res ther 2009; 11: R17 Disclosure of Interest: None declared